Question and Answers Forum

All Questions      Topic List

Trigonometry Questions

Previous in All Question      Next in All Question      

Previous in Trigonometry      Next in Trigonometry      

Question Number 35654 by chakraborty ankit last updated on 21/May/18

if  cos^2 θ−sin^2 θ=tan^2 ∅  Then proof that  2cos^2 ∅−1=cos^2 ∅−sin^2 ∅=2tan^2 θ

ifcos2θsin2θ=tan2Thenproofthat2cos21=cos2sin2=2tan2θ

Answered by tanmay.chaudhury50@gmail.com last updated on 21/May/18

cos^2 θ−sin^2 θ=tan^2 ∅   that means  cos2θ=tan^2 ∅  2cos^2 ∅−1  =cos2φ  =((1−tan^2 ∅)/(1+tan^2 ∅))  =((1−cos2θ)/(1+cos2θ))  =((2sin^2 θ)/(2cos^2 θ))  =tan^2 θ  pls check^

cos2θsin2θ=tan2thatmeanscos2θ=tan22cos21=cos2ϕ=1tan21+tan2=1cos2θ1+cos2θ=2sin2θ2cos2θ=tan2θplscheck

Terms of Service

Privacy Policy

Contact: info@tinkutara.com